Burkina Faso : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2016)
This Selected Issues paper examines the impact of scaled-up public investment in Burkina Faso. The results suggest that 'big-push' investment efforts, while designed to accelerate growth, are likely to run up against significant absorption-capacity constraints. These constraints will diminish the efficiency of investment spending and result in lower public capital accumulation and productivity growth than under a more measured approach. The empirical evidence from the experience of many countries also suggests that the results of aggressive scaling-up initiatives are mixed.